# Whoever can figure out why this doesn't work gets virtual 1337.

a+a = a+x

2a=a+x

2a-2x=a+x-2x

2(a-x) = (a-x)

2=1

No clues, it's very simple, and anyone familiar with their internets should find a humorous surprise within the solution.

a=x

a+a = a+x

2a=a+x

2a-2x=a+x-2x

2(a-x) = (a-x)

2=1

No clues, it's very simple, and anyone familiar with their internets should find a humorous surprise within the solution.

a+a = a+x

2a=a+x

2a-2x=a+x-2x

2(a-x) = (a-x)

2=1

No clues, it's very simple, and anyone familiar with their internets should find a humorous surprise within the solution.

active| newest | oldest2(a - x) = a - x

And therefore, the only solution is a-x = 0 or a=x, which is what you started with. Your conclusion "2=1" is stupidly based on division by zero.